Pelatihan Pembuatan Tempe Berbahan Dasar Kacang Merah Dalam Upaya Meningkatkan Minat Berwirausaha Mahasiswa - Oktarina, Harti; Aswad, Sitti Hajar; Athirah, Putri; Humardani, Ryan (Yayasan Daarul Huda Kruengmane, 2024)
This training on making tempeh from red beans aims to increase students' interest in entrepreneurship. Red bean tempeh is an innovative product that has great market potential, considering its nutritional content and health benefits. This activity is carried out with a participatory approach that directly involves students in the process of making tempeh, starting from preparing ingredients, fermentation process, to packaging. The results of this training showed that students' practical skills increased, as well as opening their insights into business opportunities in the food industry. Thus, this training encourages students to be more courageous in entrepreneurship and create locally-based healthy food products.